Pembinaan Panduan Pengguna Kendaraan Bermotor untuk Keselamatan Berlalu Lintas pada Siswa Yayasan Sahabat Cendikia - Nofriani Fajrah; Sri Zetli; Muhammat Rasid Ridho; Yera Wahda Wahdi (LPPM Universitas Putera Batam, 2022)
Currently, the increase in the number of motorized vehicles is increasingly out of control, for all ages of riders. More and more riders of motorized vehicles among men and women even at this age, teenagers are already using motorized vehicles. This causes problems for motorized road users, namely the increase in traffic accidents, congestion for which it is not clear what causes, and even violations of traffic signs by motorized road users. This is because road users do not pay attention to and ignore traffic rules. In particular, this is most often done by motorized vehicle road users under the age of or teenagers who do not yet have a driving license. Based on these conditions, there is a need for community service regarding the Motorized Vehicle User Guide for driving safety for the Sahabat Cendikia Foundation Students. Sahabat Cendikia Foundation is one of the non-formal educational institutions to help the community obtain formal education certificates (Package B and Package C). Therefore, it is necessary to do dedication so that guidance can be given to Sahabat Cendikia Foundation students to pay attention to driving safety for other road users. Friends of the Cendikia Foundation students participated in this service activity because some of the students there were also minors. It is hoped that with this coaching activity, the Sahabat Cendikia Foundation students understand driving safety. In addition, it is hoped that this training will reduce traffic accidents. This service activity is carried out by providing material on motorised vehicle user manuals for traffic safety and traffic sign regulations.